2017
DOI: 10.18203/2349-3291.ijcp20171727
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis in late onset sepsis

Abstract: Background: Neonatal sepsis contributes substantially to neonatal morbidity and mortality and is an ongoing major global public health challenge. In developed countries, this incidence of neonatal meningitis is 0.3 per 1000 live births. In developing countries, the reported incidence of neonatal meningitis is much higher at 0.8-6.1 per 1000 live births, with a mortality of 40-58%. So, this study was undertaken to estimate the incidence of meningitis in late onset sepsis.Methods: This study was conducted in out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The prevalence of neonatal meningitis in clinical sepsis at the Neonatal Intensive Care Unit, Sanglah General Hospital Denpasar was 68.8% [7]. A study by Arora et al also reported 55 cases of meningitis (61.11%) in 90 patients with suspected late-onset neonatal sepsis [8].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The prevalence of neonatal meningitis in clinical sepsis at the Neonatal Intensive Care Unit, Sanglah General Hospital Denpasar was 68.8% [7]. A study by Arora et al also reported 55 cases of meningitis (61.11%) in 90 patients with suspected late-onset neonatal sepsis [8].…”
Section: Introductionmentioning
confidence: 97%
“…It can cause a delay in diagnosis and in turn, affect the prognosis and survival of patients [10]. The mortality rate in neonates with meningitis in suspected late-onset sepsis was 45.5% [8]. Based on this background, we need to identify the risk factors of bacterial meningitis in late-onset neonatal sepsis at Sanglah General Hospital, Denpasar.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is the most common cause of newborn mortality, accounting for 30 to 50 percent of all neonatal fatalities each year [1]. Early onset sepsis (EOS) and late onset sepsis (LOS) are two types of neonatal sepsis [4]. In the first month, it is characterized by signs and symptoms of infection, with or without bacteremia in the first month of life.…”
Section: Introductionmentioning
confidence: 99%
“…8 In another study, meningitis in LOS was 61.1%. 9 Researches done to look for frequency of meningitis in LOS have been found to have variability while very limited work is seen at local level in this regard. The findings of this study were thought to help us in better understanding the burden of meningitis among LOS in our https://doi.org/10.29309/TPMJ/2020.27.11.4600 population while it will also open doors for newer research protocols looking at priorities for the management of affected patients.…”
Section: Introductionmentioning
confidence: 99%